Bats and viruses : a new frontier of emerging infectious diseases - Wang, Lin-fa; Cowled, Christopher (Hoboken, New Jersey : Wiley-Blackwell, 2015)
Approximately 75% of emerging infectious diseases are zoonoses, and the rate of emergence of zoonotic diseases is on the rise. Bats are being increasingly recognised as an important reservoir of zoonotic viruses of different families, including SARS coronavirus, Nipah virus, Hendra virus and Ebola virus. Understanding bats' role in emerging zoonotic diseases is crucial to this rapidly expanding area of research. Bats and Viruses: From Pathogen Discovery to Host Genomics provides an updated overview of research focusing on bat biology and the role bats play as hosts of many major zoonotic viruses. The text covers bat biology, immunology, and genomics. Chapters also delve into the various major bat-borne virus families, including lyssaviruses, paramyxoviruses, coronaviruses, filoviruses and reoviruses, among others. Edited by leaders in the field, Bats and Viruses: From Pathogen Discovery to Host Genomics is a timely, invaluable reference for bat researchers studying microbiology, virology and immunology, as well as infectious disease workers and epidemiologists, among others.
The uniqueness of bats / Paul A. Racey -- Viruses in bats : a historic view / Charles H. Calisher -- Bat iyssaviruses / Ivan Kuzmin and Charles Rupprecht -- Bat paramyxoviruses / Danielle E. Anderson and Glenn A. Marsh -- Bat coronaviruses / Xingye Ge, Ben Hu and Zhengli Shi -- Bat filoviruses / G.D. Maganga, V. Rougerona, E.M. Leroy -- Bats and reverse transcribing RNA and DNA viruses / Gilda Tachedjian, Joshua A. Hayward and Jie Cui -- Bat reoviruses / Claudia Kohl and Andreas Kurth -- Other bat-borne viruses / Suxiang Tong, Krista Queen, Mang Shi and Larry J. Anderson -- Anthropogenic epidemics : the ecology of bat-borne viruses and our role in their emergence / Jon Epstein and Hume Field -- Are bats really 'special' as viral reservoirs? what we know and need to know / Kevin J. Olival, Cristin C. Weekley and Peter Daszak -- Animal models of recently emerged bat-borne viruses / Jackie Pallister and Deborah Middleton -- Bat genomics / James J. Wynne and Mary Tachedjian -- Bat immunology / Michelle L. Baker and Peng Zhou.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Bats as carriers of disease; Bats as carriers of disease; MEDICAL -- Forensic Medicine; MEDICAL -- Preventive Medicine; MEDICAL -- Public Health; Bats as carriers of disease; Electronic books; Electronic books